Behavioral Stereotype Verbalization in Ukrainian and Polish Phraseological Pictures of the World (Linguostylistic Studies, 2020)
This article highlights results of a contrastive analysis of the Ukrainian and Polish phraseological analogues that denote various behavioral models and stereotypes; similar phraseological units from languages in question are divided into several categories, each of which is further analyzed regarding differences and similarities of the verbal expression of the key images. Phraseological equivalents of common Slavic origin, that show structural and semantic similarity of Polish and Ukrainian analogues, are classified as interlingual. The contrastive analysis of the phraseological units under investigation enables distinction of a vast group of collocations that underwent metaphorical transformations, as contrasted to a relatively small category of word combinations whose meaning is equal to the sum of meanings of their components. Research into the semantic features of phraseological expressions of human behavior and human psychic and physical states results in differentiating the following categories of idioms in Polish and Ukrainian languages: 1) those identifying untruthful actions or false information about a person; 2) identifying intention to deceive the speaker; 3) identifying situations of mindless acts; lack of discretion, etc.; 4) identifying situations resulting from psychophysical  manifestation of anger, rage, or nervousness; 5) those identifying treachery, hypocrisy, slyness, insincerity of a person who is hiding their intentions; 6) those identifying stereotypes about a greedy person; 7) those identifying a pertinacious person; 8) those identifying traits of subservience, compliance, patience; 9) those identifying a carefree person; 10) those identifying a stereotype of a quiet person. The study has revealed that absolute equivalents among Ukrainian and Polish phraseological units are numerous, which means that many share forms, semantics, and pragmatic parameters altogether, possessing identical (either positive or negative) expressive and metaphorical components. Yet the most interesting issue for contrasting proved to be phraseological equivalents that fully demonstrate original linguistic, cultural, and ideological viewpoints of the nations, as well as the patterns of mind and behavior of people-representatives of their nation.
Keywords: linguistic picture of the world; phraseological component; phraseological analogues in Ukrainian and Polish languages; behavioral stereotype; contrastive analysis